Perhitungan Subsidi Bus Trans Metro Pekanbaru Koridor III - Windu Alif Pangestu; Hendra Taufik; Sri Djuniati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Bus Trans Metro Pekanbaru (TMP) is a mass public transportation that operates in Pekanbaru City with transit working system, which aims to improve public transportation services in Pekanbaru City. Pekanbaru City Government officially launched the TMP bus on June 18, 2009, it has been 9 years since the first TMP bus was operated. It is necessary to analysis of Vehicle Operational Cost (BOK ) and calculation of the subsidi, to know total subsidi TMP bus in a day. The result of the analysis of BOK in 2017 is Rp.8.628 per seat-km per year. The result of the subsidi TMP bus corridor III is Rp.676.553. So the next step is find and analyze the alternative problem-solving simulation then that alternative can be used for investment of TMP bus corridor III become worthy of investment and profit financially. Keywords: Trans Metro Pekanbaru, Corridor III, Vehicle Operational Cost, calculation of the subsidi, Alternative Problem Solving Simulation